2020
DOI: 10.1111/eip.13085
|View full text |Cite
|
Sign up to set email alerts
|

The MAC‐P program: A pilot study of a mindfulness and compassion program for youth with psychotic experiences

Abstract: Background The purpose of this pilot study was to determine the feasibility, acceptability and the potential clinical utility of a novel mindfulness and compassion program (MAC‐P) designed for youth with a range of psychotic experiences. Method A non‐randomised, non‐controlled prospective follow‐up study was conducted. Eighteen participants who either met criteria for the ‘at risk mental state’ or were experiencing a psychotic episode or had a recent diagnosis of schizophrenia attended the 8‐week program. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…RCT 50 14. (a) Hickey et al [ 71 ] (b) Hickey et al [ 72 ] Community mental health services Mindfulness and compassion program None 1 × 90 min sessions/week for 8 weeks Feasibility and acceptability 4. Quantitative Descriptive 100 15.…”
Section: Resultsmentioning
confidence: 99%
“…RCT 50 14. (a) Hickey et al [ 71 ] (b) Hickey et al [ 72 ] Community mental health services Mindfulness and compassion program None 1 × 90 min sessions/week for 8 weeks Feasibility and acceptability 4. Quantitative Descriptive 100 15.…”
Section: Resultsmentioning
confidence: 99%
“…Only eight studies described the cultural and linguistic diversity of the sample, defined as being born in non-English speaking countries (n = 7, Hall et al, 2021;Hayes et al, 2011;Killackey et al, 2017McGuire et al, 2021;Pearce et al, 2020;Sabbioni et al, 2018) or do not speak English at home (n = 1, Kehoe et al, 2014), yet the specific countries were often not specified. There was also a lack of inclusion and reporting on the sexual and gender diversity of young people in the reviewed studies (n = 4): two studies each included two young people who identified as non-binary or gender queer (i.e., do not identify as male or female, Hall et al, 2021;Hickey et al, 2020); one study reported that 3% of the sample identified as transgender or gender diverse (Goel et al, 2021); and 15% of young people identified as same-sex attracted or bisexual in Daubney et al' (2021) study. Only five studies discussed families' socioeconomic status, encompassing parental income, educational attainment or employment, which were considered representative of the general population (Bassilios et al, 2017;Farrell et al, 2012;Havighurst et al, 2015;Hides et al, 2011;Kehoe et al, 2014).…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Sixteen of the 37 studies evaluated the impact of a therapy-based program for young people, predominantly delivered by a psychologist. Nine of the 16 studies implemented a manualized group therapy program, which included: family-based group Cognitive Behavioral Therapy (CBT) program for youth with obsessive compulsive disorder (OCD, Farrell et al, 2012); the Cool Kids program, which implemented CBT for youth with anxiety disorders (Hudson et al, 2015); origami and mindfulness-based art therapy group program (Edwards & Hegerty, 2018); Emotion Regulation and Impulse Control (ERIC) modularized CBT skills-based program (Hall et al, 2021); the Mindfulness and Compassion group program for young people experiencing psychosis (Hickey et al, 2020); the BEST MOOD program-a manualized eight-session family systems group therapy program (i.e., parent and young person sessions) to alleviate depressive symptoms (Poole et al, 2018); Tuning in to Teens, a six-session group therapy program specifically targeted to parents to help support their adolescents to understand and cope with their emotions in a positive way (Havighurst et al, 2015;Kehoe et al, 2014); and a five-session mindfulness-based group program called Taming the Adolescent Mind (Tan & Martin, 2015). Group programs were conducted weekly at local community centers or services and ranged in duration from one to three months.…”
Section: Therapy Programsmentioning
confidence: 99%
See 2 more Smart Citations